Reconstitution of Gloeobacter Rhodopsin with Echinenone: Role of the 4-keto Group - Balashov, Sergei P. (2010)
In previous work we reconstituted salinixanthin, the C(40)-carotenoid acyl glycoside that serves as a light-harvesting antenna to light-driven proton pump xanthorhodopsin, into a different protein, gloeobacter rhodopsin expressed in E. coli, and demonstrated that it transfers energy to the retinal chromophore (Imasheva et al. 2009. Biochemistry 48, 10948). The key to binding of salinixanthin was the accommodation of its ring near the retinal β-ionone ring. Here we examine two questions: do any of the native Gloeobacter carotenoids bind to gloeobacter rhodopsin, and does the 4-keto group of the ring play a role in binding. There is no salinixanthin in Gloeobacter violaceous, but a simpler carotenoid, echinenone, also with a 4-keto group that lacks the acyl glycoside, is present in addition to β-carotene and oscillol. We show that β-carotene does not bind to gloeobacter rhodopsin, but its 4-keto derivative, echinenone, does and functions as a light-harvesting antenna. This indicates that the 4-keto group is critical for the carotenoid binding. Further evidence for this is that salinixanthol, an analogue of salinixanthin in which the 4-keto group is reduced to hydroxyl, does not bind and is not engaged in energy transfer. According to the crystal structure of xanthorhodopsin, the ring of salinixanthin in the binding site is turned out of the plane of the polyene conjugated chain. Similar conformation is expected for echinenone in the gloeobacter rhodopsin. We suggest that the 4-keto group in salinixanthin and echinenone allows for the twisted conformation of the ring around C6-C7 bond and probably is engaged in interaction that locks the carotenoid in the binding site.